Forensic application of the luminol reaction as a presumptive test for latent blood detection - Barni, F.; Lewis, Simon; Berti, A.; Miskelly, G.; Lago, G. (Elsevier, 2007)
The forensic application of the luminol chemiluminescence reaction is reviewed. Luminol has been effectively employed for more than 40 years for the presumptive detection of bloodstains which are hidden from the naked eye at crime scenes and, for this reason, has been considered one of the most important and well-known assays in the field of forensic sciences. This review provides an historical overview of the forensic use of luminol, and the current understanding of the reaction mechanism with particular reference to the catalysis by blood. Operational use of the luminol reaction, including issues with interferences and the effect of the luminol reaction on subsequent serological and DNA testing is also discussed.